Design and development of automation system for precision approach path indicator (PAPI) in airfield lighting / Shah Rizal Mohd Shaher - Shah Rizal, Mohd Shaher (2018)
Airfield Grounding lighting (AGL) is the aid for the pilot to take off and land, it consists of the structure of lights, power supply, mounting systems and control from the air traffic control tower to substation and to lights. AGL are divided into three main parts, which are power supply, lighting and control system. In this project, we focused only on the lighting part that gives an aid to the pilot for safe landing by using a 3-degree slope of runway. It is called Precision Approach Path Indicator (PAPI) which is the most important light in airfield lighting. PAPI is a valuable visual aid that can provide precision direction for pilots when making a landing. Normally PAPI is a single bar with four units located on the left side of a runway for touch-down aiming point, whilst in some airports PAPI are installed in 2 bars on left and right side. To maintain operational conditions and precision of the system, PAPI must be calibrated once a year and maintenance must be carried out periodically. The calibration is done by using special tools and manually adjust the angle of the PAPI as instructed by the flight calibration team provided by the department of civil aviation authority. While carrying out PAPI calibration, the access to the runway will be blocked and all aircraft will be rescheduled. The inspection on PAPI is made by checking each of PAPI angle as specified in ICAO annex 14 which are 2.50°, 2.83°, 3.17°and 3.50°. This is very time consuming as the calibration needs to be done manually and extra man power is needed to communicate with aircraft calibration. Also, if mis-align then consume time to re align. The more time taken to conduct this exercise the more cost will be incurred to pay to the department of civil aviation authority. In this project, an automated PAPI calibration system is designed by using PAPI system and Leadscrew Stepper Motor on AutoCAD SOLIDWORKS. Then, design ladder Diagram has been constructed to simulate operation of stepper motor combined with PAPI system for automatic movement. Design model of Leadscrew stepper motor is integrated on PAPI system and helped to move the PAPI up and down (vertically) to adjust elevation angle of PAPI system. This design will allow automatic adjustment of the system and subsequently it would reduce the cost of maintenance on extra man power, special tools, safety and the most important factor is less time consuming.